DO STUDENTS AT JERASH UNIVERSITY USE NEW TECHNOLOGIES? - Aljaraideh, Yousef Ahmad (European Scientific Journal, ESJ, 2013)
This study aimed to identify that whether students at Jerash University are using new technologies or no. To achieve this goal, qualitative analysis face to face interviews were conducted with s selected sample. The sample of the study consisted of (35) students who were randomly chosen from the faculty of educational science in the academic year 2010-2011. The semi structured interview was developed in order to obtain profound knowledge and more details. The results of the study showed that students at Jerash University use new technology moderately for educational research purposes. The results of the study also revealed data show, personal computer, laptops, interactive boards and internet were broadly used. Finally, the study recommended that the necessity to update technologies at Jerash University and holding some training courses could improve the using of new technologies by the students.